JAWDAT SA’ID ON PACIFISM AND VIOLENCE TODAY - Sabina Abdulaev (CMES (Center of Middle Eastern Studies), 2024)
Nonviolence and pacifism are widely recognized and understood by various religions and cultures. Since the 1960s, a particular group of intellectuals, theologians, and religious leaders in the Muslim world have been working to establish a theoretical basis for social justice and a society that embraces diversity. Their efforts primarily focus on minimizing the use of violence. The main objective of this work is to elucidate the philosophical perspective on pacifism in Islam as articulated by the contemporary Islamic scholar Jawdat Saʽīd (1931-2022). Saʽīd offers an academic viewpoint on the strategic implementation of pacifism for promoting social change within the Muslim world and its diplomatic utilization externally. His theory is equally applicable to the non-Muslim world, encompassing monotheists and atheists as well. This study examines the texts or written materials, as well as the spoken words and interviews available on Saʽīd's personal website and other online platforms related to academia and widely known and used by the public.